Emergence of micro datacenter (cloudlets/edges) for mobile computing - Bahl, Victor (2015)
Despite major advances in technology, resource poverty continues to limit the type of applications we are able to run on our mobile devices. The challenging issue is, this constraint is fundamental and not simply a temporary limitation of current technology. This talk will put forth a vision that breaks free of this constraint. In this vision, mobile users seamlessly use nearby micro datacenters to obtain the resource benefits of cloud computing without incurring wide area network delays and jitter. Crisp interactive response for immersive applications that augment human cognition become easier to achieve. While much engineering and research remains, the concepts and ideas introduced open the door to a new world of disaggregated clouds in which seamless cognitive assistance for wireless users and new IoT applications can be delivered anyplace, anytime using the latest and greatest computer science technologies known to us.